Repeat expansion detection in neurodegenerative diseases with CRISPR/Cas9-targeted long read sequencing - Phua, Kimberly (Nanyang Technological University, 2022)
Neurodegenerative diseases are broadly characterised by degeneration and loss of neurons in the brain over time which affects the quality of life of affected individuals. Recently, new associations of repeat expansions with various neurodegenerative diseases have been reported and point to a landscape of genomic alterations that have not been well-studied in neurodegenerative diseases. Current methods used to assess repeat expansions are laborious and time-consuming. I optimised a third-generation long read sequencing strategy by Oxford Nanopore Technologies for targeting the repeat expansion genes HTT, NOTCH2NLC, C9orf72 and RFC1 using CRISPR/Cas9 and applied this to eleven patient samples to determine repeat numbers across these genes. I also tested the feasibility of utilising this method for concurrent assessment of the four repeat expansion genes in a single assay. Our results show that the method can be used to identify expanded repeat lengths and that concurrent assessment of multiple repeat expansion genes is achievable. However, further optimisation is required to improve CRISPR/Cas9 target efficiency. Overall, CRISPR/Cas9- targeted ONT sequencing is a simple and quick method for identifying repeat expansions. Thus, further improving this repeat assessment method may soon allow quick diagnosis of repeat expansion-associated neurodegenerative diseases with repeat length assessment by CRISPR/Cas9-targeted ONT sequencing.